Harmonization of Pharmacovigilance Regulation in Brazil: Opportunities to Improve Risk Communication - Varallo, Fabiana Rossi; Forgerini, Marcela [UNESP]; Herdeiro, Maria Teresa; Mastroianni, Patricia de Carvalho [UNESP] (Elsevier B.V., 2019)
Brazilian pharmacovigilance regulations involve 3 spheres: health services, Marketing Authorization Holders (MAHs), and sanitary agency. Drug tolerability began to be effectively assessed in Brazil after the founding of the National Agency of Sanitary Surveillance, which developed the Sentinel Network Project, The objective of the Sentinel Network Project is to increase the adverse drug reaction (ADR) reporting rate by health care professionals in the hospital setting. Pharmacovigilance practices became mandatory for MAHs, and patient tolerability issues were considered in drug policy in Brazil only as recently as 2000. However, despite recent events, the regulatory advancements in pharmacovigilance in Brazil are only equivalent to international practices (ie, those of the European Union). The pharmacovigilance system in the European Union integrates the national authorities, the European Commission, and the European Medicines Agency, which is responsible for the scientific evaluation, supervision, and safety monitoring of medicines for human and veterinary use in the European Union. Furthermore, ADR patient reporting is included in the new EU pharmacovigilance regulations. Numerous possible ways are available to improve the Brazilian pharmacovigilance system, mainly through regulations of biosimilar, nanotechnology, and veterinary medicines or by training health care professionals and patients to report nonserious cases and quality deviations. It is necessary to encourage and develop strategies for decentralizing pharmacovigilance actions in the whole country, as is common practice in several EU countries. Motivating and considering ADR reports by patients and improving feedback and audit practices in health care services and MAHs are also necessary measures. With the inclusion of Brazil as a member of the International Conference of Harmonization, significant changes in pharmacovigilance regulation are expected; these updates, which will consider international standards, will improve signal detection and risk communication. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Drug Safety; Patient Safety; Pharmacovigilance; Risk Management; Pharmaceutical Regulation